Pengembangan Bahan Ajar Digital Teks Cerita Fantasi Bermuatan Karakter bagi Siswa Kelas VII Smp - Iis Jubaedah; Abdul Rozak; Yusida Gloriani (Jurnal Pendidikan Edutama, 2023)
Abstract: The background in this research is because of the importance of instilling character education in learning and the use of digital teaching materials that are still rarely used. There is no alternative media for textbooks as a learning resource for students to learn Indonesian, especially fantasy story text material. This study aims to explain the development of digital fantasy story text teaching materials that include character values in learning fantasy story texts for seventh grade junior high school students. This type of research uses the ADDIE development method which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were seventh grade students of SMP Negeri 1 Jalaksana and SMP Islam Terpadu Al-Multazam 2. The results obtained from the analysis of the average teacher needs of 92% strongly agreed about the need for digital teaching materials to instill character values through story text learning. fantasy and 100% requires digital media materials in learning Indonesian, especially fantasy story texts. Analysis of student needs 87% of students said they wanted media containing images, animation, video, and sound and 81% of students agreed when studying in the laboratory using a laptop/computer with digital learning media. For the feasibility of digital teaching materials, the material expert score is 2900 points, media expert is 2640 points, graphic design expert is 1800, practitioners are 2340 points, the Indonesian language teacher response test is 30620 points with a total overall score of three experts and practitioners getting 40300 points, with a percentage score of 86.11 included in the very good criteria. These results indicate that the learning media for developing digital teaching materials for fantasy story texts containing character education for class VII is in the "Very Good" category or is suitable for use without revision. Digital teaching materials for fantasy story texts have character education values that have met the requirements of discipline, polite, religious, independent, environmental care, social care, responsibility, and honesty.  Keywords: Teaching materials, Digital, fantasy stories, character education  Abstrak: Latar belakang dalam penelitian ini adalah karena pentingnya menanamkan pendidikan karakter dalam pembelajaran dan penggunaan bahan ajar digital yang masih jarang digunakan. Belum ada media alternatif buku teks sebagai sumber belajar bagi siswa untuk belajar bahasa Indonesia, khususnya materi teks cerita fantasi. Penelitian ini bertujuan untuk menjelaskan pengembangan bahan ajar teks cerita fantasi digital yang memasukkan nilai karakter dalam pembelajaran teks cerita fantasi siswa kelas VII SMP. Jenis penelitian ini menggunakan metode pengembangan ADDIE yang terdiri dari lima tahap yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian ini adalah siswa kelas VII SMP Negeri 1 Jalaksana dan SMP Islam Terpadu Al-Multazam 2. Hasil penelitian diperoleh dari analisis kebutuhan rata-rata guru sebesar 92% sangat setuju mengenai kebutuhan bahan pengajaran digital untuk menanamkan nilai-nilai karakter melalui pembelajaran teks cerita fantasi dan 100% memerlukan bahan media digital dalam pembelajaran bahasa Indonesia  khususnya teks cerita fantasi. Analisis kebutuhan siswa 87% siswa mengatakan menginginkan media yang berisi gambar, animasi, video, dan suara dan 81% siswa menyatakan setuju apabila belajar di laboratorium dengan  menggunakan laptop/komputer dengan media pembelajaran  digital. Untuk kelayakan bahan ajar digital diperoleh skor ahli materi sebesar 2900 poin, ahli media sebesar 2640 poin, ahli desain grafis sebesar 1800, praktisi sebesar 2340 poin, uji respon guru bahasa Indonesia sebesar 30620 poin dengan total skor keseluruhan dari tiga ahli dan praktisi  memperoleh sebesar 40300 poin, dengan presentase skor 86,11 termasuk ke dalam kriteria sangat baik. Hasil tersebut menunjukan bahwa media pembelajaran pengembangan bahan ajar digital teks cerita fantasi bermuatan pendidikan karakter bagi kelas VII berada pada kategori “Sangat Baik”  atau layak digunakan tanpa revisi. Bahan ajar digital teks cerita fantasi memiliki muatan nilai pendidikan karakter sudah memenuhi yaitu disiplin, santun, religius, mandiri, peduli lingkungan, peduli sosial, tanggung jawab, dan kejujuran Kata Kunci: Bahan ajar, Digital, Cerita fantasi, Pendidikan karakter